2017
DOI: 10.1080/03007995.2017.1321532
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathic pain: a narrative review of etiology, assessment, diagnosis, and treatment for primary care providers

Abstract: The purpose of this narrative review is to provide a brief high-level overview of NeP for primary healthcare providers that includes a discussion of mechanisms, prevalence, burden, assessment, and treatment. The information provided here should help primary care providers better understand this type of chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Antidepressants and anticonvulsants are conventional treatments for neuropathic pain. The currently recommended first-line treatments are anticonvulsants such as gabapentin and pregabalin, serotonin-norepinephrine reuptake inhibitors such as duloxetine and venlafaxine, and tricyclic antidepressants [25]. Although opioids are considered a second- or third-line treatment for neuropathic pain, controversy remains over their use [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antidepressants and anticonvulsants are conventional treatments for neuropathic pain. The currently recommended first-line treatments are anticonvulsants such as gabapentin and pregabalin, serotonin-norepinephrine reuptake inhibitors such as duloxetine and venlafaxine, and tricyclic antidepressants [25]. Although opioids are considered a second- or third-line treatment for neuropathic pain, controversy remains over their use [58].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of gabapentin in relieving neuropathic pain has been proven in many studies and is recommended as a first-line treatment [22, 23, 25]. Because of this, our study was designed as a noninferiority trial.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropathic disease is common in cancer survivors and may result from the infiltration of nerve tissue by the tumor, radiation treatment, chemotherapy, or cancer-related surgery, leading to symptoms such as pain and functional impairment (59). Schönsteiner et al, 2017 (38) have demonstrated the beneficial impact (symptoms relieve, physical fitness and sensory function) on chemotherapy-induced polyneuropathy (CIPN) of a program including massage, mobilization as well as physical exercises and WBV.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain is not a single disease entity but rather a complex syndrome that arises from a lesion or disease of the somatosensory system, either peripheral fibres or central neurons 1,2 . There are multiple chronic painful conditions of neuropathy including central post‐stroke pain, painful diabetic neuropathy, post‐herpetic neuralgia and peripheral nerve injury pain 2‐4 . The overall prevalence of neuropathic pain within the general population is estimated to be 7%‐10% and on an upwards trend owing to the ageing global population 2,5,6 .…”
Section: Introductionmentioning
confidence: 99%